2020
DOI: 10.1097/01.ogx.0000668328.82296.5d
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Carbon Footprint Analysis of Disposable and Reusable Vaginal Specula

Abstract: (Abstracted from Am J Obstet Gynecol 2020; doi: 10.1016/j.ajog.2020.02.007) In an attempt to save time, as well as reduce costs and transmission of infections, many health care systems in the United States have increased use of disposable medical equipment, which generally decrease costs upfront compared with their reusable alternatives. Use of disposable instruments, however, is associated with increased solid waste production and may increase greenhouse gas emissions, negatively impacting the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A number of studies in HICs have demonstrated reusable equipment to be environmentally superior to single-use devices (SUDs) for a wide range of equipment and procedures, potentially reducing GHG emissions by up to 90%. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 The few studies that found SUDs to be environmentally beneficial have all been conducted in Australia, where electricity is mainly generated from the carbon-intensive source of coal. 15 , 24 , 25 Environmentally preferable purchasing policies could guide the selection of equipment and consumables based on their long-term financial and environmental cost rather than their up-front cost.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies in HICs have demonstrated reusable equipment to be environmentally superior to single-use devices (SUDs) for a wide range of equipment and procedures, potentially reducing GHG emissions by up to 90%. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 The few studies that found SUDs to be environmentally beneficial have all been conducted in Australia, where electricity is mainly generated from the carbon-intensive source of coal. 15 , 24 , 25 Environmentally preferable purchasing policies could guide the selection of equipment and consumables based on their long-term financial and environmental cost rather than their up-front cost.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] Some researchers have taken this to the next level and estimated the reduction in carbon footprint by implementing certain interventions, usually which span multiple disciplines, such as energy and water savings methods, switching to reusable medical equipment, using alternative treatment options or employing new technology in health care. [24][25][26][27][28][29][30][31][32][33][34]…”
Section: Opportunities Of National Health Sector Carbon Footprint Mod...mentioning
confidence: 99%
“…For example, equipped with the knowledge of national health system carbon footprints and health care specific modelling methodology, researchers have undertaken focused carbon footprint analysis of health care facilities, of medical disciplines, of medical procedures, of specific clinical conditions and care pathways and of medical equipment 15‐23 . Some researchers have taken this to the next level and estimated the reduction in carbon footprint by implementing certain interventions, usually which span multiple disciplines, such as energy and water savings methods, switching to reusable medical equipment, using alternative treatment options or employing new technology in health care 24‐34 …”
Section: Opportunities Of National Health Sector Carbon Footprint Mod...mentioning
confidence: 99%
“…Context and setting are crucial: For example, Life-cycle Assessments (LCAs) of bioreactors in a Good Manufacturing Practices (GMP) compliant laboratory may not be transferable to non-GMP settings 16 . Equally, LCAs conducted in clinical settings may not be applicable in laboratory settings 17,18 . Here, we analyse the CO 2 equivalent (CO 2 e) footprint of utilising single-use plastics, or re-use of glass or plastic items within laboratory environments.…”
Section: Introductionmentioning
confidence: 99%